(untitled) (Yesterday & Today Journal for History Education in South Africa and abroad, 2021)
The Word Generation Programme (WordGen), produced by Harvard University Education School in 2006, presents ways of engaging with and improving literacy skills in school going students. WordGen comprises a set of freely available lesson plans, structured to be taught every day throughout the week, that focus on students engagement with material and concepts through processes of discussion, debate, and perspective taking. The materials engage the students’ everyday lives, as well as the knowledge that the unit is intended to teach. As everyday life examples are used, it is possible to imagine a contextual translation from the United States of America, to South Africa. This article explores the possibility of using the materials created by the Strategic Education Research Project (SERP) – who have pioneered the “WordGen” programme – as a basis to create materials for South African classrooms, specifically to teach History for the Intermediate Phase (Grade 4 - 6). In this article I argue that the WordGen lessons engage important skills for learning and teaching History. I outline the skills that are generated when History is taught in a compelling and iterative way and then engage with WordGen concepts and content and with the WordGen material specifically designed to teach History: SoGen. The article considers the case of third year education students at the University of Johannesburg and their responses to the WordGen material. The experiences gained from this translation into a tertiary context indicates that Word Generation may garner similar positive outcomes as those seen in the primary school context.